In Search of Dependable Design. - Hoffman, Leah (Communications of the ACM, 2008)
The article discusses the reliability of computer hardware and software, examining the manner in which developers can create more reliable designs. A number of high-visibility design flaws are presented in the article including a 1994 circuitry error in the Pentium I microprocessor made by Intel Corp. Topics include the degree to which people depend on computers, the costs of faulty software on the economy, and flaws that arise in higher-level design process. Also discussed are programs debugged by random testing and model testing.